2002
DOI: 10.1021/ie0105526
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Aqueous Phenol Wastes on Synthetic Diamond Thin-Film Electrodes

Abstract: The electrochemical oxidation of phenol in basic media using a diamond thin-film electrode has been studied. Within the parameter ranges used (temperature: 15-60 °C, initial total carbon concentration: 360-1450 mg of C dm -3 ; current density: 15-60 mA cm -2 ), almost complete mineralization of the organic waste is obtained. The mineralization rate increases with current density and temperature. Current efficiency depends mainly on mass transfer limitations: in the absence of mass transfer limitations, instant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
74
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 41 publications
7
74
0
2
Order By: Relevance
“…In order to reduce the mathematically complexity of theoretical models aimed to determine the concentrations of compounds involved in the oxidation process, Cañizares et al [38][39][40] considered some simplifying assumptions. Their model divides the electrochemical reactor into three zones: two close to the electrodes (electrochemical zones) and a third zone corresponding to the bulk of the solution (chemical zone) that can be considered as consecutive stirred-tank reactors.…”
Section: Kinetic Model Of Organics Mineralization On Bdd Anodesmentioning
confidence: 99%
“…In order to reduce the mathematically complexity of theoretical models aimed to determine the concentrations of compounds involved in the oxidation process, Cañizares et al [38][39][40] considered some simplifying assumptions. Their model divides the electrochemical reactor into three zones: two close to the electrodes (electrochemical zones) and a third zone corresponding to the bulk of the solution (chemical zone) that can be considered as consecutive stirred-tank reactors.…”
Section: Kinetic Model Of Organics Mineralization On Bdd Anodesmentioning
confidence: 99%
“…Electrochemical degradation (ECD) is one of the alternatives for degradation of these compounds, and is suitable for low-volume application and environmental compatibility [4]. In recent years, electrochemical oxidation of aqueous wastes containing non-biodegradable organics such as phenol [5], chlorophenols [6] and aniline [7] has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Studies were carried out on the influence of different electrode materials such as Pt, Au, Ni, Cu, DSA-O 2 (dimensionally stable anode), PbO 2 and boron-doped diamond electrodes, on phenolics and lignin electro-oxidation reactions (Kovalenko et al, 1977;Parpot et al, 2000;Canizares et al, 2002;Iniesta et al, 2001). Early studies on graphite, copper, platinum and nickel anodes showed that platinum and nickel produced higher amounts of aldehyde and a comparison of the nickel and DSA-O 2 anodes, at the same high current densities of 750 A/m 2 , showed that nickel produced a higher concentration of vanillin per unit of charge used (Kovalenko et al, 1977;Parpot et al, 2000).…”
Section: Introductionmentioning
confidence: 99%